Cobalamin and folate status predicts mental development scores in North Indian children 12-18 mo of age - Strand, Tor A; Taneja, Sunita; Ueland, Per M; Refsum, Helga; Bahl, Rajiv; Schneede, Joern; Sommerfelt, Halvor; Bhandari, Nita (The American journal of clinical nutrition, 2013)
Micronutrient deficiencies can affect cognitive function. Many young children in low- and middle-income countries have inadequate cobalamin (vitamin B-12) status. The objective was to measure the association of plasma concentrations of folate, cobalamin, total homocysteine, and methylmalonic acid with cognitive performance at 2 occasions, 4 mo apart, in North Indian children aged 12-18 mo. Bayley Scales of Infant Development II were used to assess cognition. In multiple regression models adjusted for several potential confounders, we measured the association between biomarkers for folate and cobalamin status and psychomotor or mental development scores on the day of blood sampling and 4 mo thereafter. Each 2-fold increment in plasma cobalamin concentration was associated with a significant increment in the mental development index score of 1.3 (95% CI: 0.2, 2.4; P = 0.021). Furthermore, each 2-fold increment in homocysteine or methylmalonic acid concentration was associated with a decrement in mental development index score of 2.0 (95% CI: 0.5, 3.4; P = 0.007) or 1.1 (95% CI: 0.3, 1.8; P = 0.004) points, respectively. Plasma folate concentration was significantly and independently associated with mental development index scores only when children with poor cobalamin status were excluded, ie, in those who had cobalamin concentrations below the 25th percentile. None of these markers was associated with psychomotor scores in the multiple regression models. Cobalamin and folate status showed a statistically significant association with cognitive performance. Given the high prevalence of deficiencies in these nutrients, folate and cobalamin supplementation trials are required to measure any beneficial effect on cognition.